Mimickers of classic acantholytic diseases. Issue 3 (March 2017) - Ho, Jonathan; Bhawan, Jag
Abstract: Acantholysis is a commonly encountered histological pattern which typically generates a differential of the pemphigus variants, Hailey–Hailey, Darier's and Grover's diseases. In addition to these diseases, the dermatologist and dermatopathologist must be aware of entities that mimic classic acantholytic dermatoses and of rare disease variants, which are characterized by acantholysis.